CRISPR–Cas9 genome engineering of primary CD4+ T cells for the interrogation of HIV–host factor interactions. Issue 1 (January 2019) - Hultquist, Judd; Hiatt, Joseph; Schumann, Kathrin; McGregor, Michael; Roth, Theodore; Haas, Paige; Doudna, Jennifer; Marson, Alexander; Krogan, Nevan
Abstract CRISPR–Cas9 gene-editing strategies have revolutionized our ability to engineer the human genome for robust functional interrogation of complex biological processes. We have recently adapted this technology for use in primary human CD4+ T cells to create a high-throughput platform for analyzing the role of host factors in HIV infection and pathogenesis. Briefly, CRISPR–Cas9 ribonucleoproteins (crRNPs) are synthesized in vitro and delivered to activated CD4+ T cells by nucleofection. These cells are then assayed for editing efficiency and expanded for use in downstream cellular, genetic, or protein-based assays. This platform supports the rapid, arrayed generation of multiple gene manipulations and is widely adaptable across culture conditions, infection protocols, and downstream applications. Here, we present detailed protocols for crRNP synthesis, primary T-cell culture, 96-well nucleofection, molecular validation, and HIV infection, and discuss additional considerations for guide and screen design, as well as crRNP multiplexing. Taken together, this procedure allows high-throughput identification and mechanistic interrogation of HIV host factors in primary CD4+ T cells by gene knockout, validation, and HIV spreading infection in as little as 2–3 weeks. In this protocol, the authors describe how to design, synthesize, and deliver CRISPR–Cas9 RNPs to primary CD4+ T cells for targeted gene knockout. They then show how the edited cells can be used for the analysis of host factors in HIV replication.